A3 Domain Is Essential for Interaction of von Willebrand Factor with Collagen Type III - Lankhof, Hanneke L; van Hoeij, Maggy; Schiphorst, Marion E; Bracke, Madelon; Wu, Ya-Ping; Ijsseldijk, Martin J W; Vink, Tom; de Groot, Philip G; Sixma, Jan J (Thrombosis and Haemostasis, 1996)
von Willebrand factor (vWF) mediates platelet adhesion at sites of vascular damage. It acts as a bridge between receptors on platelets and collagens present in the connective tissue. Two collagen binding sites have been identified on the A1 and A3 domain of the vWF subunit. To study the functional importance of these binding sites, we have made two deletion mutants that lack the A1 domain (residues 478-716; ΔA1-vWF; Sixma et al. Eur. J. Biochem. 196,369,1991 [1]) or the A3 domain (residues 910-1113; ΔA3-vWF). After transfection in baby hamster kidney cells overexpressing furin, the mutants were processed and secreted efficiently. Ristocetin or botrocetin induced platelet binding was normal for ΔA3-vWF as was binding to heparin and factor VIII. As reported by Sixma et al. (1) ΔAl-vWF still binds to collagen type III, indicating that the A3 domain is sufficient for the interaction. In the current study, we investigated the binding of ΔA3-vWF to collagen type III. When preincubated on collagen type III it did not support platelet adhesion under flow conditions, whereas it was able to support platelet adhesion when coated directly to a glass surface. The binding of 125I-ΔA3-vWF to collagen was specific but maximal binding was about 40 times less compared to 125I-vWF. When added at 25 times excess, ΔA3-vWF did not compete with 125I-vWF for binding to collagen type III, whereas ΔAl-vWF did. The binding of 125I-ΔA3-vWF could be blocked by excess unlabeled vWF but not by ΔA1-vWF. In conclusion, we demonstrate that the A3 domain in vWF contains the major collagen binding site. The major binding site present on the A3 domain and the minor site present on A1 bind to different sites on collagen.